The Approximation of Bivariate Blending Variant Szász Operators Based Brenke Type Polynomials - Behar Baxhaku; Ramadan Zejnullahu; Artan Berisha (Advances in Mathematical Physics)
We have constructed a new sequence of positive linear operators with two variables by using Szasz-Kantorovich-Chlodowsky operators and Brenke polynomials. We give some inequalities for the operators by means of partial and full modulus of continuity and obtain a Lipschitz type theorem. Furthermore, we study the convergence of Szasz-Kantorovich-Chlodowsky-Brenke operators in weighted space of function with two variables and estimate the rate of approximation in terms of the weighted modulus of continuity.